2007
DOI: 10.1177/0269215506070254
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of shoulder pain after traumatic brain injury

Abstract: There is a relatively high prevalence of shoulder pain after traumatic brain injury. Trauma to the shoulder complex contributes to shoulder pain after traumatic brain injury, making clinical presentation different from people with stroke. The findings support the need for greater attention in the management of shoulder pain after traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We also identified a number of studies reporting on the prevalence of pain and headache among TBI patients [33–51]. Headache was the most common pain complaint among TBI patients in one prospective cohort and several cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified a number of studies reporting on the prevalence of pain and headache among TBI patients [33–51]. Headache was the most common pain complaint among TBI patients in one prospective cohort and several cross‐sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43] (18 cross-sectional, 5 prospective, and 3 retrospective) including 4468 patients with TBIs were identified that reported on the prevalence of chronic pain after TBI. Table 1 provides a summary of the articles selected for review in the pediatric population [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown that chronic pain is a potential complication of TBI . Prior studies have shown that patients with TBI have a high prevalence of chronic pain syndromes such as headache [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], shoulder pain [32], heterotopic ossification [33], complex regional pain syndrome [34], and peripheral nerve injuries [35]. The association of TBI with chronic pain was first described in 1915 in troops returning from World War I with "shell shock" [44].…”
Section: Introductionmentioning
confidence: 99%
“…Hemiplegic shoulder pain (HSP) is an umbrella term that is commonly used in reference to any subjective complaint of shoulder pain in a hemiparetic upper limb (1). It is a significant problem after acquired brain injury with a reported prevalence of 22-47% in stroke (2) and 62% in traumatic brain injury (3). Resolution rates are generally lowjust 14% to 27% of cases in stroke (1,4).…”
Section: Introductionmentioning
confidence: 99%